Integrating Self-Hypnotherapy Techniques into Physical Conditioning Programs for Volleyball Performance Enhancement (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study examined the effects of integrating self-hypnotherapy techniques into physical conditioning programs on volleyball players’ performance. Using a quasi-experimental design with pre-test and post-test control groups, 20 volleyball athletes aged 17–19 were purposively sampled and divided into experimental (n=10) and control (n=10) groups. The experimental group received 6–8 weeks of combined physical training and self-hypnotherapy sessions (20 minutes per training), while the control group engaged in physical training alone. Key performance variables measured included physical attributes (agility, endurance, power), psychological indicators (competitive anxiety, confidence, focus), and volleyball skills (passing, spiking, blocking, serving). Results indicated significant improvements in the experimental group compared to controls. Agility increased by 12.5% (p < 0.01), endurance by 15.3% (p < 0.01), and power by 10.8% (p < 0.05). Psychological assessments showed a 22% reduction in anxiety levels (p < 0.001) and increased confidence and focus by 18% and 20%, respectively (p < 0.01). Volleyball skill performance also improved notably, with effect sizes ranging from moderate to large (Cohen’s d = 0.6–0.9). The control group showed moderate gains but significantly less than the experimental group. These findings highlight the efficacy of self-hypnotherapy as a complementary approach to enhance both physical and psychological aspects of volleyball performance. Incorporating self-hypnotherapy into conditioning programs may optimize athletes’ overall readiness and competitive success.